Ispol'zovanie gelii-neonobogo lazera dlya vosstanovleniiya i povysheniya rabotosposobnosti - Dolmatova, T. I.; Shraiberg, G. L.; Bliznets, N. I. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this study was to reveal the HNL opportunities of the helio-neon laser (HNL) using for the biologically active points influencing 30 elite athletes acted as the subjects. As a result of the research it had become possible to conclude, that all the athletes, irradiated by HNL demonstrated the expressed araising of the sporting working capacity in the cycle of the training lessons. The rehabilitation process was going much better in the athletes of experimental groups than in control one. It can be considered that the revealed changes of theactivity and reactivity in the sympathetic-adrenal system are layed in the basis of the mechanisms of laseropuncture's influences on athletes.